Lacticaseibacillus kribbianus sp. nov., isolated from pig farm faeces dump. Issue 11 (30th November 2022) - Paek, Jayoung; Bai, Lu; Shin, Yeseul; Kim, Hongik; Kook, Joong-Ki; Kim, Si Hyun; Shin, Jeong Hwan; Chang, Young Hyo
Abstract : A lactic acid bacteria isolated from pig faeces was characterized using a polyphasic approach. Cells of the strain were Gram-stain-positive, rod-shaped and facultative anaerobic. Phylogenetic analysis of 16S rRNA gene sequence indicated that the isolate belonged to the genus Lacticaseibacillus ; however, the similarity to other homologues within the genus was <98 %. Analysis of housekeeping gene sequences ( pheS and recA ) revealed that the strain formed a sub-cluster adjacent to Lacticaseibacillus absianus and Lacticaseibacillus daqingensis . The main fatty acids of the strain is the C18 : 1 ω9 c and C16 : 0 . The G+C content of the genomic DNA was 62.8 mol %. The major polar lipids were diphosphatidylglycerol, phosphatidylglycerol, aminophospholipids and phospholipids. The cell-wall peptidoglycan did not contain meso -diaminopimelic acid. Thus, YH-lac21 T (=KCTC 21185=JCM 34953) represents a novel species. The name Lacticaseibacillus kribbianus sp. nov. is proposed.